Trilhando o abandono: discutindo sobre o processo de degradação urbana nos espaços da estação nova de Campina Grande-PB - Carvalho, Gabriel Lincoln Lopes (2023)
To commemorate the fiftieth anniversary of the arrival of the train to the city of Campina Grande-PB and to meet the demands of the railway sector, in 1957, construction began on its second railway station, "Estação Nova", of the Rede Ferroviária do Nordeste, which had buildings, support sheds and a larger maneuvering area. After the railway heyday, there was a sum of processes and negative contexts for the railways that influenced a gradual decline until deactivation. Following what happened on the national scene, Campina Grande deactivated passenger transport in the 1980s; the Old Station was listed by IPHAEP and today it is used as a Cotton Museum and its physical structure has been maintained, on the other hand, the New Station was not valued as a heritage; was forgotten by the government and heritage agencies, being a victim of material and sense abandonment, resulting in its railway yard and buildings in a state of ruins and deterioration, currently serving as a scenario of social pathologies, also had its frames pilfered, buildings roofed off and accumulation of residual waste. The main objective of this work was to carry out a case study in the spaces of Estação Nova de Campina Grande, seeking to analyze the causes and consequences of abandonment in relation to the historical, political, patrimonial, infrastructure and social aspects that transformed the rail yard. The cartographic method was used, combined with document analysis and bibliographical review, for its development. As results achieved, a dynamic portrait of the process of transformation of the railway yard was built, through historical, patrimonial, built environment and spatial syntax analyses. An analysis methodology was generated to evaluate the abandonment and in the case study the chronology of the events and the main reasons that caused the deactivation and fomented the current state of abandonment and degradation were traced. This research also developed an in-depth analysis of related railway equipment, with the characterization of important national and international examples that had conflicting periods/deactivations. With this analysis, it was possible to understand correlations and processes that caused many railway equipment to be abandoned, and others to be rebuilt with new uses, which complemented the study of strategies and potential for reuse of the spaces of the Campina Grande station developed.